Attempted Suicide, Self-Harm, and Psychological Disorder Among Young Offenders in Custody. (July 2015) - Moore, Elizabeth; Gaskin, Claire; Indig, Devon
This study aims to identify risk factors for suicide and self-harm among young offenders. The data are from the 2009 New South Wales Young People in Custody Health Survey. The sample ( N = 313) were 88% male and 48% Aboriginal. Sixteen percent reported ever having suicidal thoughts and 10% reported a suicide attempt. Twenty-one percent reported thoughts of self-harm and 16% reported actual self-harm. Female young offenders reported higher rates of suicidal behavior and self-harm compared to males. Significant correlates of attempted suicide and self-harm included childhood adversity and psychiatric disorder. This study finds that young offenders are at high risk of suicidal and self-harm behaviors. Early identification and support among this vulnerable group are critical.